Solution
We are given the two equations
![\begin{gathered} 2x-y=4\ldots\ldots\ldots\ldots\ldots\ldots\text{.}(1) \\ 4x-2y=6\ldots\ldots\ldots.\ldots\ldots\text{.}(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r5jkp2tv3i24aoo944doqgrzg3fzdxkx9z.png)
Now, equation (1) x 2
![\begin{gathered} 4x-2y=8\ldots\ldots.\ldots\ldots\ldots\ldots\ldots(1) \\ 4x-2y=6\ldots\ldots\ldots\ldots\ldots\ldots.\ldots(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gdijajuq0a5yg3gbxxaspbtdt06jkevrrb.png)
Equation (1) - equation (2)
![\begin{gathered} (4x-4x)+(-2y-(-2y))=8-6 \\ 0+0=2 \\ 0=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d37zmm5pbyevwgwqlskrf16g03nfny3en4.png)
Which is never possible!
Therefore, the system of equation is NOT consistent.
Note:
Let us also draw the graph of the eqautionm given
Therefore, the system of equation is Inconsistent and Independent